Evaluation of Vav3.1 as prognostic marker in endometrial cancer - Boesch, Maximilian; Sopper, Sieghart; Marth, Christian; Fiegl, Heidi; Wiedemair, Annemarie; Rössler, Julia; Hatina, Jiri; Wolf, Dominik; Reimer, Daniel; Zeimet, Alain G (Journal of cancer research and clinical oncology, 2018)
PURPOSE: Vav3 is a guanine nucleotide exchange factor that regulates the activity of Rho/Rac family GTPases. In a study on ovarian cancer, we recently demonstrated pronounced prognostic and predictive value of Vav3.1, a specific truncation variant of the parental Vav3 gene. Here, we sought to investigate the role of Vav3.1 in the most prevalent gynecological tumor entity, endometrial cancer. METHODS: Vav3.1 transcript levels were determined in a large cohort of endometrial cancer patients using variant-specific PCR (n = 239), and non-malignant endometrial tissue served as control (n = 26). Expression levels of Vav3.1 were stratified according to established clinicopathological characteristics and correlated to long-term patient survival (average follow-up of > 7.5 years). Type 1 and type 2 cancers were separately investigated. RESULTS: While Vav3.1 was markedly overexpressed in endometrial cancer tissue, we could not detect associations with clinical parameters related to prognosis, such as FIGO stage and tumor grade. Kaplan-Meier estimators of different measures of survival failed to show prognostic significance of Vav3.1 in endometrial cancer. Lack of prognostic value was observed for both type 1 and type 2 cancers. CONCLUSIONS: Our study shows that Vav3.1 is not suited as a marker of cancer progression and/or treatment response in endometrial cancer. Feasibility and potential benefit of targeting Vav3.1 in endometrial cancer needs to be evaluated in future studies, proceeding from its clear, roughly ten-fold, induction in the malignant endometrium.
Keywords: serózní cystadenokarcinom; lidé středního věku; studie případů a kontrol; retrospektivní studie; senioři nad 80 let; Aged, 80 and over; míra přežití; Combined Modality Therapy; nádorové biomarkery; Endometrial Neoplasms; Humans; Middle Aged; Survival Rate; Biomarkers, Tumor; senioři; protoonkogenní proteiny c-vav; prognóza; Protein isoform; Prognosis; Female; Vav3; Adenocarcinoma, Clear Cell; následné studie; Cancer; Endometrial cancer; Aged; adenokarcinom z jasných buněk; Case-Control Studies; Transcript variant; ženské pohlaví; Proto-Oncogene Proteins c-vav; Retrospective Studies; Follow-Up Studies; kombinovaná terapie; protein - isoformy; Adult; nádory endometria; dospělí; lidé; Guanine nucleotide exchange factor; Protein Isoforms; Cystadenocarcinoma, Serous